The political conflict between the regulation and deregulation of bioprospecting in Antarctica - Arroyo Cortes, Cristián (Revista Tribuna Internacional, 2019)
Bioprospecting is an issue discussed at the Antarctic Treaty Consultative Meetings since several years ago. However, there are not substantive advances in the enactment of regulations about it. The discussions on this matter are analyzed.